Optimizing Synergistic Metabolism in Xenobiotic Biodegradation: Engineering a Pseudomonas Putida Based Microbial Consortium (American Journal of Life Science and Innovation, 2023)
This study focuses on the engineering of a microbial consortium, incorporating Pseudomonas putida and selected members, to enhance synergistic metabolism for xenobiotic biodegradation. The aim is to explore the potential of microbial interactions in environmental remediation. The engineered consortium underwent iterative optimization to fine-tune microbial ratios. Metabolomic and transcriptomic analyses were employed to investigate metabolic interactions within the consortium. Xenobiotic biodegradation efficiency was evaluated through controlled laboratory experiments. The engineered microbial consortium exhibited a significant synergistic effect, demonstrating enhanced biodegradation capabilities compared to individual monocultures. The iterative optimization process led to a substantial increase in biodegradation efficiency. Metabolomic and transcriptomic analyses provided valuable insights into the metabolic interactions within the consortium. The study successfully engineered a microbial consortium for efficient xenobiotic biodegradation, showcasing the potential of microbial interactions in environmental remediation. The optimized consortium composition and advanced analytical techniques offer promising avenues for sustainable bioremediation practices. Further research is warranted to explore broader applications and address potential scalability challenges.